PORTRAIT OF RELIGIOUS FUNDAMENTALISM AMONG STUDENTS OF THE STUDY PROGRAM ISLAMIC EDUCATION - Dewi, Putri (Adaara: Jurnal Manajemen Pendidikan Islam, 2022)
The term fundamentalism is often associated with extreme attitudes, rigidity, conservativeness, stagnation, conservativeness, and resistance to progress, so that many people shy away from the labeling of the term. Avoiding the use of non-neutral terms as above, in this study the term fundamentalism will be returned to its basic meaning, namely returning to religion in a "full" and literal way free from compromise, taming, and reinterpretation.This type of research is quantitative research, where the author makes students of the Islamic religious education study program at IAIN Parepare as objects. The researcher used a questionnaire as an instrument and used the Rasch Model research method. The purpose of this study was to describe the most dominant tendencies and factors in religious fundamentalism among students of the Islamic Religious Education study program.Based on the research conducted, it was concluded that students of the Islamic Religious Education study program IAIN Parepare had moderate and fundamental tendencies which were balanced with 80 total respondents, there were 34 people (42%) tended to be moderate. There are as many as 34 people (42%) tend to be fundamental. However, in the description of the discussion of respondents' tendencies, the most dominant type of dimension among the five dimensions is the IT dimension (Intolerance).Â